Relative Toxicity of Some Conventional Insecticides Against Adult Beetles of Calopepla leayana Latr. (Chrysomelidae : Coleoptera) - Gupta, B. K.; Ahmed, S. I.; Veer, Vijay (Indian Forester, 1989)
Twenty two conventional insecticides were tested as direct spray against adult beetles of Calopepla leayana. This is a serious pest of Gmelina arborea plantations and occurs all along the tract of its host plant. The relative effectiveness of these insecticides was in order of Formothion> Monocrotophos> Quinalphos> Chlordimeform> gamma-BHC> Malathion + Fenitrothion > Toxaphene> Malathion> Dichlorvos (Nuvan) > Pyrethrum> Klofos > Endosulfan > Bromophos-ethyl > Fenitrothion > Dieldrin> D.D.T. > Aldrin> Chlordane> Dichlorvos (DDVP)> Methyl parathion.